Turkey Energy and Environment Review : Synthesis Report - World Bank (Washington, DC, 2014)
Gaps in knowledge about the interface between energy and the environment, were identified sometime in the late 1990s, and a number of studies were then conceived to address this knowledge gap, and advance the level of understanding, by collecting additional information, through specialized analyses. This Synthesis Report summarizes the results of ten studies, collectively referred to as the "Energy and Environment Review", covering energy demand forecasting; environmental issues associated with the coal/lignite, mining and power generation sub-sector; potential of co-generation in Turkey; assessment of transmission and distribution loss reduction; improved management of emissions from non-power sectors; improvement of petroleum fuels quality; and, technical support to implement various energy system analyses. This report comprises a discussion of the issues relating to the energy and environment; a description of the key findings and recommendations; and a summary an conclusions.